2023
DOI: 10.1002/cctc.202201386
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Electron Mediator Transparency: Photocatalytic Hydrogen Production from Polyoxometalate using Dye‐double‐layered Photocatalysts

Abstract: One-directional electron transfer is crucial for two-step photoexcitation (Z-scheme) water-splitting photocatalysis. We investigated the hydrogen evolution activity of PS-double-layered photocatalysts (X-DSP, X-RuCP 6 -Zr-RuP 6 @Pt/K x H 4-x Nb 6 O 17 ; X = Zr 4 + , H + ) in the presence of highly charged polyoxometalates-(Mn II -POM)-as redox-reversible electron donors, to induce effective photocatalyst-donor electrostatic attraction. Surfacephosphonate-comprising H + -DSP completely one-electron oxidized V I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
(103 reference statements)
0
1
0
Order By: Relevance
“…In the current research, a high rate of hydrogen production by Pd-Rb 2 O@g-C 3 N 4 /TiO 2 was observed, indicating that the back reaction was completely suppressed. 67…”
Section: Photocatalytic Water Splitting Mechanismmentioning
confidence: 99%
“…In the current research, a high rate of hydrogen production by Pd-Rb 2 O@g-C 3 N 4 /TiO 2 was observed, indicating that the back reaction was completely suppressed. 67…”
Section: Photocatalytic Water Splitting Mechanismmentioning
confidence: 99%
“…In terms of catalysis, these materials could serve as Brønsted acids and possess tunable redox potentials enable efficient charge separation and multielectron transfer processes with other species under mild conditions, and thus play a crucial role in the field of photocatalysis. [21][22][23][24][25][26] However, the features of good solubility and easily transferred structural patterns have posed limitations on the widespread application of POMs in catalytic systems. It may lead to undesired leaching or migration of active species during the catalysis, which might compromise the efficiency and stability of the POMs-based catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, POMs can be easily modified by incorporating different functional groups or metal ions, allowing for tailored properties and enhanced functionalities. In terms of catalysis, these materials could serve as Brønsted acids and possess tunable redox potentials enable efficient charge separation and multielectron transfer processes with other species under mild conditions, and thus play a crucial role in the field of photocatalysis [21–26] . However, the features of good solubility and easily transferred structural patterns have posed limitations on the widespread application of POMs in catalytic systems.…”
Section: Introductionmentioning
confidence: 99%